Anodal tDCS during face-name associations memory training in Alzheimer's patients - Cotelli, Maria; Manenti, Rosa; Brambilla, Michela; Petesi, Michela; Rosini, Sandra; Ferrari, Clarissa; Zanetti, Orazio; Miniussi, Carlo (Frontiers in Aging Neuroscience, 2014)
Objective: Given the limited effectiveness of pharmacological treatments, non-pharmacological interventions to treat Alzheimer’s disease (AD) have gained attention in recent years. The aim of the present study is to investigate the effects of anodal tDCS (AtDCS) combined with memory training on face-name associations in an AD patient sample. Methods: 36 AD patients were randomly assigned to one of three study groups: Group 1, AtDCS plus individualized computerized memory training; Group 2, placebo tDCS plus individualized computerized memory training; Group 3, AtDCS plus motor training. Results: A general improvement in performance was observed after two weeks of memory training. Both the anodal tDCS plus individualized computerized memory training and the placebo tDCS plus individualized computerized memory training groups had significantly improved performances at two weeks compared with the AtDCS plus motor training group. Conclusion: Our findings suggest a beneficial effect of individualized memory rehabilitation in AD patients.